Strong effect of magnetic field on the edge luminescence line width in diluted magnetic narrow-gap Hg₁₋xMnxTe - Mazur, Yu.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1998)
Peculiarities of photoluminescence in narrow-gap Hg₁₋xMnxTe (0.09 < x < 0.11) under variation of both magnetic field and temperature are studied. A strong resonance enhancement of the edge emission and a narrowing of the line width to less than 2.5 meV were detected. The photoluminescence behaviour observed can be well described by the model of a magnetically trapped exciton.